2010
DOI: 10.1111/j.1600-9657.2010.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of dental trauma among mothers in Mangalore

Abstract: Most of the mothers were graduates and were aware of the emergency management of dental trauma. The working mothers had better knowledge and awareness regarding mouth guards (72%) when compared with non-working mothers (37%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
4
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 11 publications
2
43
4
9
Order By: Relevance
“…Unfortunately, about 39.3% of the parents in the present study answered that they will not clean the avulsed tooth before going to the dentist and it was found to be slightly more (31%) when compared with the study by Oliveira et al (14) When the immediate re-implantation is not performed, storage mediums that can aid in pulpal and periodontal healing are milk, sterile saline solution, saliva. But in the present study, most of the parents responded that they would immerse the avulsed tooth in tap water (41.3%), which was found to be different when compared to the studies reported by Hegde et al (16) The lack of experience and knowledge expressed by the parents answering the questionnaire concerning dental trauma reflects the need for more effective communication between dental 405 professionals and parents to enable them to act correctly when facing a case of dental avulsion. Additionally, educational campaigns and preventive programs on dental trauma must be organized to improve caregivers' knowledge on emergency management of dental avulsion.…”
Section: Discussion:-contrasting
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, about 39.3% of the parents in the present study answered that they will not clean the avulsed tooth before going to the dentist and it was found to be slightly more (31%) when compared with the study by Oliveira et al (14) When the immediate re-implantation is not performed, storage mediums that can aid in pulpal and periodontal healing are milk, sterile saline solution, saliva. But in the present study, most of the parents responded that they would immerse the avulsed tooth in tap water (41.3%), which was found to be different when compared to the studies reported by Hegde et al (16) The lack of experience and knowledge expressed by the parents answering the questionnaire concerning dental trauma reflects the need for more effective communication between dental 405 professionals and parents to enable them to act correctly when facing a case of dental avulsion. Additionally, educational campaigns and preventive programs on dental trauma must be organized to improve caregivers' knowledge on emergency management of dental avulsion.…”
Section: Discussion:-contrasting
confidence: 99%
“…In the present study, only 18.7% of the parents were aware of the immediate re-implantation of an avulsed tooth, similar to a study reported by Al-Jundi, (15) In contrast, to that reported by Oliveira et al, (14) (39%) and (66.6%), by Hegde et al, (16) which clearly indicates the insufficiency in the knowledge about the immediate management of avulsed tooth. Therefore, the parents need to be educated more in this aspect.…”
Section: Discussion:-supporting
confidence: 86%
“…20 'nın çalışmasında kuru ortamda saklama %45, Hegde ve ark. 15 21 . Benzer şekilde dişin peçete vb.…”
Section: Tablo-1: Ebeveynlerin Dental Yaralanmalarla Ilgili Genel Görunclassified
“…Hedge ve ark. 15 yaptıkları çalışmada avülse olan dişi yerine yerleştirmeyen ebeveynlerin oranını %64,8 olarak belirtmektedir. Murali ve ark.…”
Section: Introductionunclassified
“…A maior parte dos dentes avulsionados por traumatismos é perdida e quando reimplantados, podem apresentar, a longo prazo, necrose pulpar, calcificações e reabsorções radiculares 17 . Estudos [18][19][20][21][22][23][24][25][26][27][28] realizados em diferentes países têm demonstrado que o conhecimento, tanto de pessoas leigas como de profissionais (professores, educadores físicos, cirurgiões-dentistas e médicos) sobre traumatismos dentários é inadequado e, com isso, possíveis sequelas não são reduzidas. Um estudo realizado na Jordânia 4 mostrou que 43,1% das crianças procuraram tratamento dentário apenas quando complicações tardias apareceram e o tempo entre o traumatismo e a procura por tratamento odontológico variou entre 2 horas e 3 anos.…”
Section: Introductionunclassified